Interest rate hysteresis in macroeconomic investment under uncertainty - Ansgar Belke; Matthias Göcke (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
The interest rate is generally considered as a monetary policy tool and, at the same time, via Tobin's q, as an important driver of macroeconomic investment. As an innovation, this paper derives the exact shape of the "hysteretic" impact of changes in the interest rate on macroeconomic investment under the scenarios of certainty and uncertainty. We capture the direct interest rate-hysteresis effects on investment and the capital stock and, explicitly, stochastic changes of the interest rate-investment hysteresis relationship. Starting with hysteresis effects on a microeconomic level of a single firm, we apply an explicit aggregation procedure to derive the interest rate-hysteresis effects on a macroeconomic level. Based on our simple model we are quite skeptical regarding the efficacy of the central bank in providing incentives for macroeconomic investment in times of low or even zero interest rates and high uncertainty. Only if the central bank implements monetary policy strategies such as "forward guidance" and is able to credibly commit to low interest rates also for the foreseeable future, our quite strong verdict may be of less relevance. – – Der Zinssatz wird im Allgemeinen als ein bedeutsames geldpolitisches Instrument, aber gleichzeitig auch über Tobin's q als ein wichtiger Treiber makroökonomischer Investitionen angesehen. Als Innovation leitet dieses Papier die genaue Form der "hysteretischen" Auswirkungen von Zinsänderungen auf makroökonomische Investitionen. Es unterscheidet dabei zwischen den beiden Szenarien "Sicherheit" und Unsicherheit". Wir erfassen die direkten Effekte der Zinshysterese auf Investitionen und den Kapitalstock und explizit auch stochastische Veränderungen der hysteretischen Beziehung zwischen Zinsen und Investitionen. Ausgehend von Hystereseeffekten auf der mikroökonomischen Ebene eines einzelnen Unternehmens wenden wir ein explizites Aggregationsverfahren an, um die Zinshystereseeffekte auf makroökonomischer Ebene abzuleiten. Auf der Grundlage unseres einfachen Modells sind wir bezüglich der Wirksamkeit der Zinspolitik einer Zentralbank im Hinblick auf die Stimulierung makroökonomischer Investitionen in Zeiten niedriger oder gar Nullzinsen und hoher Unsicherheit recht skeptisch. Nur wenn die Zentralbank geldpolitische Strategien wie "Forward Guidance" umsetzt und sich auch in absehbarer Zeit glaubwürdig zu niedrigen Zinsen verpflichten kann, dürfte unser recht starkes Urteil weniger relevant sein.
Keywords: C61; E22; E44; 330; forward guidance; interest rate; investment; Mayergoyz-Preisach model; monetary policy; path dependence; non-ideal relay; sunk-cost hysteresis; uncertainty; zero lower bound